Your Error’s Got me Feeling – How Empathy Relates to the Electrophysiological Correlates of Performance Monitoring - Thoma, Patrizia; Bellebaum, Christian (Frontiers in Human Neuroscience, 2012)
The error-related and feedback-related negativities (ERN and FRN) represent negative event-related potentials associated with the processing of errors and (negative) response outcomes. The neuronal source of these components is considered to be in the anterior cingulate cortex (ACC). Monitoring one’s own behaviour and the impact it may have on other people or observing other individuals perform and receive feedback for their actions may also engage empathy-related processes. Empathy is conceived of as a multifaceted construct involving both cognitive and affective components, partly also supported by the ACC. The present mini-review aims to summarize the sparse database linking the electrophysiological correlates of performance monitoring to empathy. While most studies so far provide largely indirect evidence for such an association – e.g. by pointing towards altered ERN/ FRN signalling in populations characterized by deviations in empathic responding – fewer investigations establish more explicit links between the two concepts. The relationship between state and, less consistently, trait measures of empathy and action monitoring might be more pronounced for observational than for active participation.